THE CATEGORY OF SPACE IN ENGLISH AND UZBEK - Рузимуратова Нилуфар Рузимурот кизи (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this article explores some of the key notions of the construct “concept” from the psychological and educational literature in order to demonstrate the need for standardization of definition and a moreunified front in future investigations involving this important element in the study of cognition. Furthermore, it will be discussed that the relationships between categorization and concept and some features.